(untitled) (Journal of Engineering, 2011)
Particulate matter (PM) emitted from diesel engine exhaust have been measured in terms of mass, using 99.98 % pure ethanol blended directly, without additives, with conventional diesel fuel (gas – oil),to get 10 % , 15 %, 20 % ethanol emulsions . The resulting PM collected has been compared with those from straight diesel. The engine used is a stationary single cylinder, variable compression ratio Ricardo E6/US. This engine is fully instrumented and could run as a compression or spark ignition. Observations showed that particulate matter (PM) emissions decrease with increasing oxygenate content in the fuel, with some increase of fuel consumption, which is due to the lower heating value of ethanol. The reduction in PM formation increased with load increase, maximum reduction were 58% at 1800 rpm. There was no significant reduction observed at low loads. It could be concluded from the test results that ethanol may be an alternative to / or partially substitute, fossil fuels.